Construction of Inner Conflict Meaning in Song Lyrics “Ego” by Rizky Febian - Novi Amelia Ramadhan; Vika Vika; Khaerudin Imawan (Journal of Social Research, 2025)
This study aims to construct the meaning of inner conflict in the lyrics of the song “Ego” by Rizky Febian through Roland Barthes' semiotic approach. The main issue that is the focus of this study refers to how the meaning of inner conflict is constructed through song lyrics as a medium of self-expression in interpersonal relationships. The song “Ego” was chosen because of its strong emotional resonance and its theme, which touches on awareness of egoism and its impact on the dynamics of interpersonal relationships. This study employs a qualitative method using text analysis as the primary research technique. Primary data is obtained from an analysis of the song lyrics based on Roland Barthes' semiotic perspective, which classifies meaning into three levels: denotation, connotation, and myth, while secondary data is obtained from documentation and fan comments on online platforms. The analysis results show that the lyrics of the song “Ego” depict emotional struggles and sacrifices in maintaining relationships, even if it means sacrificing oneself and personal feelings. This reflects the psychological dynamics of individuals and the prevailing ideology in society regarding love and selfishness. In conclusion, the song “Ego” is not merely a form of personal expression by the singer but also reflects a culture that tends to justify sacrifice in imbalanced interpersonal relationships. This study contributes to understanding how Indonesian K-pop music serves as a complex medium for self-expression and social reflection